The impact of CES1 genotypes on the pharmacokinetics of methylphenidate in healthy Danish subjects. (24th February 2017) - Stage, Claus; Jürgens, Gesche; Guski, Louise Schow; Thomsen, Ragnar; Bjerre, Ditte; Ferrero‐Miliani, Laura; Lyauk, Yassine Kamal; Rasmussen, Henrik Berg; Dalhoff, Kim; ,
Abstract : Aims: This study investigated the influence of CES1 variations, including the single nucleotide polymorphism (SNP) rs71647871 (G143E) and variation in copy number, on the pharmacokinetics of a single oral dose of 10 mg methylphenidate. Methods: CES1 genotype was obtained from 200 healthy Danish Caucasian volunteers. Based on the genotype, 44 (19 males and 25 females) were invited to participate in an open, prospective trial involving six predefined genotypes: three groups with two, three and four CES1 copies, respectively; a group of carriers of the CES1 143E allele; a group of individuals homozygous for CES1A1c ( CES1VAR) ; and a group having three CES1 copies, in which the duplication, CES1A2, had increased transcriptional activity. Plasma concentrations of methylphenidate and its primary metabolites were determined at scheduled time points. Results: Median AUC of d ‐methylphenidate was significantly larger in the group carrying the 143E allele (53.3 ng ml −1  h −1, range 38.6–93.9) than in the control group (21.4 ng ml −1  h −1, range 15.7–34.9) ( P  < 0.0001). Median AUC of d ‐methylphenidate was significantly larger in the group with four CES1 copies (34.5 ng ml −1  h −1, range 21.3–62.8) than in the control group ( P  = 0.01) and the group with three CES1 copies (23.8 ng ml −1  h −1, range 15.3–32.0, P  = 0.03). There was no difference between the groups with two and three copies of CES1 . Conclusions: The 143E allele resulted in an increased AUC, suggesting a significantly decreased CES1 enzyme activity. Surprisingly, this was also the case in subjects with homozygous duplication of CES1, perhaps reflecting an undiscovered mutation affecting the activity of the enzyme.